"Epigramma (Inscription) for a Woman Who is in Labour but Cannot Give Birth": A Re-writing of a Birthing Amulet - Afentoulidou, Eirini (Byzantinische Zeitschrift, 2025)
In what is now its last folio, codex Laurentianus Plutei 57.40, a major witness of Michael Psellos’ epistolary and rhetorical works dated to the beginning of the 12th century, transmits a short text titled "Epigramma for a woman who is in labour but cannot give birth". The text is otherwise unattested. Yet, one can recognise elements known from texts meant to be written on birthing amulets that circulated in various languages and regions throughout Late Antiquity, the Middle Ages, and beyond. What is unique in this short text is that it intentionally departs from the traditional discourse of amulets: known amuletic formulas are rewritten in ways that associate them with other genres - starting with the term "Epigramma" in the title. Furthermore, interest in it stems from the fact that it is one of the very rare testimonies for a birthing amulet that has survived from the Byzantine period. In this article, the text is edited for the first time. Moreover, the article attempts to trace the underlying amuletic formulas and analyse the process of rewriting.